﻿Neurosarcoidosis presenting as trigeminal nevralgia: a case report and review of the literature - ﻿Braksick, S.; ﻿Shah-Haque, S.; ﻿El-Haddad, B.; Moussa, R. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Sarcoidosis is a granulomatous disease that can present systemically, but primarily has pulmonary manifestations. It is reported across all races, but has a higher incidence among African Americans. Neurological involvement in sarcoidosis is rare, with cranial nerve seven being the most commonly reported neurological finding. Trigeminal neuralgia, as presented in this case, is very rare. A 38-year-old African American female, with history of refractory trigeminal neuralgia, cutaneous sarcoidosis, and an extensive psychiatric history, presented to the hospital for fifth cranial nerve decompression. She had failed medical therapy and gamma knife therapy. Prior to surgery, magnetic resonance imaging (MRI) revealed a mass of 1.5 cm x 0.6 cm x 1.1 cm in the left Meckel’s cave, which, when compared with prior imaging, was not present. A partial craniotomy was done to excise the mass. Frozen pathological sections showed granulomatous inflammation consistent with sarcoidosis. Stains for acid fast bacilli and fungi remained negative. Quantiferon Gold and HIV serum studies were negative. High resolution computed tomography (CT) scan the chest showed patchy infiltrates in the lungs that presented as chronic interstitial lung disease. The patient’s neurological symptoms resolved after surgical resection. She was dismissed home on a tapering dose of dexamethasone and follow-up with a rheumatologist. This case illustrates that when a patient with sarcoidosis presents with neurological symptoms, neurosarcoid should be considered. Most cases are diagnosed during autopsies. Recognizing and correctly diagnosing neurosarcoid leads to proper treatment and decreased morbidity in patients.